2014
DOI: 10.1111/hel.12163
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Helicobacter pylori Infection 2014

Abstract: This review summarizes important studies regarding H.pylori therapy published from April 2013 to April 2014. The main themes that emerge are assessing the efficacy of standard triple therapy, as well as exploring new first-line treatments, predominantly optimized triple therapies and non-bismuth quadruple schemes. Regarding newer non-bismuth quadruple regimens, the compliance and tolerance seem to be similar for sequential and concomitant regimens. Notably, no study yet has demonstrated a clear statistical sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 69 publications
0
15
0
6
Order By: Relevance
“…Seven-day triple therapy with a proton pump inhibitor (PPI), amoxicillin, and clarithromycin is the recommended first-line therapy for H. pylori eradication in most countries. However, the efficacy of this triple therapy is in decline because of increased antibiotic resistance (Vakil and Megraud 2007;Graham and Shiotani 2008;Papastergiou et al 2014;O'Connor et al 2014). The appearance of superbacteria has increased this concern, and developing a safe and effective therapy has become a common goal among scientists in this field.…”
Section: The Therapeutic Efficacy Of Ccf In Balb/c Micementioning
confidence: 99%
“…Seven-day triple therapy with a proton pump inhibitor (PPI), amoxicillin, and clarithromycin is the recommended first-line therapy for H. pylori eradication in most countries. However, the efficacy of this triple therapy is in decline because of increased antibiotic resistance (Vakil and Megraud 2007;Graham and Shiotani 2008;Papastergiou et al 2014;O'Connor et al 2014). The appearance of superbacteria has increased this concern, and developing a safe and effective therapy has become a common goal among scientists in this field.…”
Section: The Therapeutic Efficacy Of Ccf In Balb/c Micementioning
confidence: 99%
“…20 Recently, O'Connor and associates observed that some probiotics, such as Lactobacilli and Bifidobacteria, exert an anti-H pylori effect in vitro and were helpful in reducing antibiotic-related side effects. 26 The most frequently studied agents have been Lactobacillus sp. strains.…”
Section: Probiotics As Adjuvant Therapy For Helicobacter Pylori Eradimentioning
confidence: 99%
“…The rising resistance to clarithromycin requires the introduction of sequential or concomitant therapy as the first option, especially for the areas with high resistance to clarithromycin. Levofloxacin in combination with different antibiotics showed a good therapeutic effect as the first, second or third line therapy but arriving problem is the emergence of resistance to fluoroquinolones 5,6 . In a study from Japan newer fluoroquinolones sitafloxacin, which shows the lowest minimum inhibitory concentration for H. pylori, proved to be effective in combination with PPI, amoxicillin and metronidazole as third line therapy 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Quadruple therapy with bismuth, like fluoroquinolones, has proved effective as a first line therapy or as rescue therapy. The main reason for the increased resistance to antibiotics is point mutations which accumulate in the H. pylori DNA 5 .…”
Section: Introductionmentioning
confidence: 99%